Two new species of Eutarsopolipus (Acari: Prostigmata: Podapolipidae) parasitizing Syntomus lateralis (Coleoptera: Carabidae) from Iran - Hajiqanbar, Hamidreza; Mortazavi, Abdolazim; Khaustov, Alexandr (Zootaxa, 2019)
Two new species of the genus Eutarsopolipus Berlese (Acari: Heterostigmata: Podapolipidae), Eutarsopolipus gombrooni Hajiqanbar and Mortazavi sp. nov. and E. oconnori Hajiqanbar and Mortazavi sp. nov., are described from different localities in Iran. Both belong to the myzus species group and were found beneath the elytra of Syntomus lateralis (Motschulsky) (Coleoptera: Carabidae). The carabid genus Syntomus is a new host record for mites of the genus Eutarsopolipus.